2019
DOI: 10.1111/ajsp.12371
|View full text |Cite
|
Sign up to set email alerts
|

Cultural difference in maladaptive functions of perfectionistic self‐presentation

Abstract: Perfectionistic self-presentation (PSP), which describes an expressive aspect of perfectionism in the interpersonal domain, is a defensive form of perfectionism that has been relatively understudied. Although existing evidence obtained from Western societies has consistently shown maladaptive functions of PSP, the question of whether these patterns are universal remains unanswered. The current research explored the potential moderating effect of culture by evaluating whether the negative influence of PSP is we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
(94 reference statements)
0
5
0
Order By: Relevance
“…Cross‐culture research showed that in‐group perception may be stronger in collectivistic societies than in individualistic societies (Zourrig, Chebat & Toffoli, ). The strength of a certain factor in promoting or impairing the sense of agency and control can also vary across different cultures (Wang, Li & Xie, in press). Future research should explore whether we can replicate the patterns in individualistic multicultural societies, such as the United States and Canada.…”
Section: Discussionmentioning
confidence: 99%
“…Cross‐culture research showed that in‐group perception may be stronger in collectivistic societies than in individualistic societies (Zourrig, Chebat & Toffoli, ). The strength of a certain factor in promoting or impairing the sense of agency and control can also vary across different cultures (Wang, Li & Xie, in press). Future research should explore whether we can replicate the patterns in individualistic multicultural societies, such as the United States and Canada.…”
Section: Discussionmentioning
confidence: 99%
“…Responses were provided on a scale ranging from 1 ( strongly disagree ) to 6 ( strongly agree ). Higher scores (α = .86) indicate more perceived constraints (Wang et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…This is an important aspect because conclusions obtained with western samples may not be applicable to other societies. Wang et al (2019) found evidence for both universal and culturally specific patterns regarding the influence of PSP when they compared Chinese and North American participants. However, to our knowledge, no studies on PSP have been carried out in the Latin American population.…”
Section: This Studymentioning
confidence: 97%
“…Almost all the accumulated knowledge regarding perfectionism has been obtained from research carried out in the English-speaking population from North America and Europe. Thus, the relationship between culture and PSP has been ignored (Wang et al, 2019). This is an important aspect because conclusions obtained with western samples may not be applicable to other societies.…”
Section: This Studymentioning
confidence: 99%